Optimasi dan Uji Antibakteri Nanopartikel Perak dengan Bioreduktor Ekstrak Batang Anggrek Merpati (Dendrobium crumenatum Sw.) - Keiza Natania Panjaitan; Syamsurizal Syamsurizal; Indri Maharini; Diky Okta Yudha Putra; Prima Septiana (Sinteza, 2025)
Silver nanoparticles have demonstrated significant antibacterial efficacy against Escherichia coli and Staphylococcus aureus.  using a green synthesis method with plant extracts rich in flavonoids as bioreductor.  The pigeon orchid (Dendrobium crumenatum Sw.) is a plant with potential as a bioreductant, especially its stem, rich in flavonoid compounds. Optimizing heating temperature, extract volume, and silver nitrate concentration is essential for producing silver nanoparticles with optimal properties and enhanced antibacterial activity.  This research conducts optimization by varying the volume of pigeon orchid stem extract, heating temperature, and AgNO3 solution concentration.  The main parameter in the optimization is the Surface Plasmon Resonance (SPR) value. The characterization of silver nanoparticles includes particle size, polydispersity index, zeta potential, FTIR spectra, and antibacterial activity tests against E. coli and S. aureus. The research results show that the optimum conditions for synthesising silver nanoparticles are 1 mL of orchid stem extract, a heating temperature of 60°C, and an AgNO3 concentration of 1.629 mM..  The silver nanoparticles produced have characteristics with an SPR peak at 450 nm, a particle size of 98.267 nm, a polydispersity index of 0.2337, and a zeta potential of -21.9 mV.  Antibacterial tests showed an inhibition zone of 14,71±1,23 mm against S. aureus and 15,28±0,91 mm against E. coli.  These results prove that silver nanoparticles effectively inhibit the growth of gram-positive and gram-negative bacteria.